Experimental Investigation of Micro-Gas Turbine Performance at Reduced Air Inlet Temperature - Said, M.A. (EDP Sciences, 2017)
Gas turbines have long been utilized as the main device for power generator. High temperature of ambient air flowing into inlet can reduce their performance. The objective of this study is to investigate the performance of a 1.5 kW micro-gas turbine at reduced inlet temperature using dry-ice as the cooling elements. Dryice is placed surrounding the outer wall of contained in a net-like holder at the inlet before the compressor and the inlet air temperature found to be decreased till 13°C from the ambient temperature. Comparison test was performed with a baseline result, which is the operation without the dry-ice cooling unit and the results shows that the power output decreases linearly with the increase of inlet air temperature. It was recorded that increase power output of 8.5 achieved from reduction of temperature of 7.5. The power output was found also to be decreased with time, due to the inlet duct exposed to the heat form the combustion chamber. This indicates better insulation or adapted data recording approach is needed. © The authors, published by EDP Sciences, 2017.